The problem of correctness and reliability of the study in trilingual education - M.R., Kondubaeva; A. T., Ongarbaeva; N.K., Bekalay; A.K., Aubakirova; S. Sh., Berdenova; A.K., Tolkinbayev (Opción, 2019)
This article deals with the problem of correctness and reliability of experimental research methods and simulations of the basic research methods of decision the problem in a pedagogical experiment. Modeling of the educational process is used of the context with classical methods of research and modern innovative methods of self-education, co-education, cooperation and self-organization of the synergetic approach in pedagogy. In particular, the analysis and synthesis of classical scientific and methodical works on the subject of research are combined with the methods of modeling the educational process and mathematical modeling as an argumentative basis of the reliability of the results.